Peran Media Pembelajaran Video dalam Menciptakan Pembelajaran yang Menyenangkan di SMK YLA Cibadak - Yuyu Yuhaeni; Siti Qomariyah; Nurasiah Jamil (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to explore the role of video learning media in creating enjoyable learning at YLA Cibadak Vocational School. In the digital era, the use of video media has become an effective tool for presenting learning material visually and interactively, which can increase student engagement and motivation. This study uses a qualitative approach with observation, interviews and document analysis methods to collect data from teachers and students. The research results show that video learning media contributes significantly in creating an interesting and dynamic learning atmosphere. Students find it easier to understand material presented via video, especially because the visualization supports the explanation of difficult concepts. Additionally, videos provide flexibility for students to learn according to their pace and learning style. However, challenges such as limited access to technology and the need for training for teachers to maximize the use of this media still need to be overcome. This research concludes that with the right support, video learning media can be an effective tool in creating fun and meaningful learning at YLA Cibadak Vocational School.